The Lanthony D15 Color Test Can be Learned. - Ng, Jason S. (Optometry & Visual Performance, 2021)
Background: The Lanthony desaturated color vision test is a color arrangement test wherein a patient must arrange 15 caps into color order. It is a difficult test for color-normal patients and is even more challenging for color vision-deficient patients due to its low saturation, which makes the cap-color differences fairly small. Despite the challenge, this case report will show that the test may not always be reliable. Case Report: A 25-year-old Caucasian male returned to our office for continued evaluation for color vision deficiency. He had previously been diagnosed with protanopia based on anomaloscope testing, which was consistent with other color tests. The patient had previously shown learning on the easier Farnsworth saturated color test and was interested in attempting to learn a harder test. The patient was sent home with a Lanthony color test and Richmond Illuminator. He returned for follow-up testing, which showed that he was able to score perfectly on the Lanthony desaturated color test, which was very surprising. Conclusion: This case shows that for some highly motivated patients, the Lanthony D15 color test may be subverted, and knowledge of this possibility is important for clinicians to consider.